PEMBERDAYAAN IBU-IBU MELALUI LITERASI DIGITAL UNTUK MENANGKAL HOAKS DI ERA INFORMASI - Siagian, Ade Indriani; Marpaung, Agnes Monica; Dewindaru, Deanda (Jurnal Abdimas Musi Charitas, 2025)
Purpose: This study aims to strengthen digital literacy among mothers, who function as primary gatekeepers of health information within the family. The activity focuses on enhancing critical thinking, information verification skills, and awareness of misinformation risks when accessing digital health related content. Design Methodology Approach: A community based outreach intervention was conducted using the CRAP framework, which emphasizes Currency, Relevance, Authority, and Purpose in evaluating digital information. The program employed a pre test and post test design to assess changes in participants’ digital health literacy before and after the educational intervention. Findings: The findings reveal a measurable improvement in participants’ digital health literacy following the activity. Mothers demonstrated a stronger ability to critically evaluate online health information, identify unreliable sources, and recognize potential misinformation, particularly content circulated through social media and instant messaging platforms. Practical Implications: The results indicate that a simple, communicative, and context driven educational approach is effective in improving public awareness and critical evaluation skills in the digital environment. Accessible digital literacy programs are therefore essential for community empowerment, especially for vulnerable groups such as mothers who play a central role in family health decision making. Originality Value: This study highlights mothers as strategic actors in digital health information management and demonstrates that a practical CRAP based intervention can significantly enhance digital health literacy. The program contributes to the achievement of sustainable development goals related to digital skills and health literacy by empowering families to navigate digital information responsibly.